ANALYSIS OF DRUG MANAGEMENT AT THE SENGKOL HEALTH CENTER, PUJUT DISTRICT, CENTRAL LOMBOK REGENCY IN 2021 - Erna Yuliani Siti (Scientia Integritas Utama, 2022)
The purpose of this study is to determine the pattern of drug management in the Sengkol Public Health Center, Pujut District, Central Lombok Regency in terms of aspects of selection, planning, demand and acceptance, as well as drug storage. Method This research was conducted in a quantitative descriptive manner with cross sectional data collection. Quantitative data was obtained from the review of the 2021 LPLPO and RKO 2020 documents. Qualitative data was obtained from interviews with the head of finance and pharmacy staff at the Sengkol Health Center. Based on the analysis of drug management at the Sengkol Health Center, the results obtained are: drug proposals to the formulary are in accordance with standards, item conformity with Fornas (89.65%), item suitability with disease pattern (52%), sufficient funds (195%), planning accuracy (260%), suitability of request items (100%), suitability of number of requests (20.59%), suitability of receiving items (100%), suitability of receipts (460%), storage according to dosage forms (100%), storage according to temperature (100%), storage of narcotics according to regulations (0%), storage of psychotropics according to regulations (0%), storage of precursors according to regulations (0%), storage of OOT according to regulations (50%), storage of non-contaminated drugs (99 ,5%), the arrangement pays attention to FEFO (100%), high-alert drug storage (100%), and LASA drug storage (100%). So it can be concluded that the management of drugs at the Sengkol Health Center is not good, because it is not in accordance with the established standards